Digitalization of Population Data Collection to Realize Medan Krio Village as an Independent Village - ginting, devita (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
An Independent Village is a village that has sufficient availability and access to basic services, adequate infrastructure, accessibility/transportation that is not difficult, good public services and good governance. Medan Krio Village as a public service institution is responsible for ensuring that government programmes reach the community. Easy access for the community to civil registration services is one indicator of the government's success in managing civil registration services for its citizens. Law No. 25 of 2009 on public services explains that public services are activities or a series of activities aimed at fulfilling services regulated by law for all citizens and residents in the form of goods, services and administrative services provided by the government or certain organisations. As a form of effort in realising Medan Krio as one of the Independent Villages, it is necessary to digitise population data collection to facilitate village officials in recording all of its people. This research aims to digitise android-based population data collection to make it easier for village officials to access and reach their citizens so that they can provide maximum service to the community. REFERENCES Aji, R. (2016). Digitalisasi, Era Tantangan Media (Analisis Kritis Kesiapan Fakultas Dakwah dan Komunikasi Menyonsong Era Digital). Islamic Communication Journal, 01(01), 43-54. Ashari, & Sallu, S. (2023, Januari). Digitalisasi Kualitas Pelayanan Publik di Dinas Kependudukan dan Catatan Sipil. Remik: Riset dan E-Jurnal Manajemen Informatika Komputer, 7(1), 342-351. Irawanti, G. (2025). SISTEM INFORMASI MANAJEMEN DESA BERBASIS INTEGRASI APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DENGAN CASH MANAGEMENT SYSTEM (CMS) CORPORATE DI DESA EKA BAHURUI KECAMATAN MENTAWA BARU KETAPANG. Profit: Jurnal Pengabdian Kepada Masyarakat, 4(2), 30-34. Hastuti, S. H. D. (2020, Mei). Pentingnya Pemanfaatan Data Kependudukan di Era Digital. Jurnal Teknimedia, 1(1), 18-21. Hamim, A. H. (2022). Peran Layanan Digitalisasi Perpustakaan Di Lingkungan Balai Pendidikan Dan Pelatihan Keagamaan Kota Bandung. J-Staf : Siddiq, Tabligh, Amanah, Fathonah, 1(1), 26–37. Https://Doi.Org/10.62515/Staf.V1i1.18 Huntua, F. S., Tohopi, R., & Tantu, R. (2024, June). Digitalisasi Pelayanan E-KTP di Dinas Kependudukan dan Catatan Sipil Kabupaten Bone Bolango. Socius: Jurnal Penelitian Ilmu-ilmu Sosial, 1(11), 181-189. Ilham, M. (2025). Rancang Bangun Sistem Informasi Berbasis Website Pada Kantor Desa Sassa Kabupaten Luwu Utara. Peripheral: Jurnal Ilmu Komputer, 1(1), 7-12. Irwandi, M., Said, R., & Basri. (2021). Sistem Digitalisasi Administrasi Kependudukan Pada Kantor Dinas Kependudukan dan Catatan Sipil Kabupaten Polewali Mandar. Jurnal Pengabdian Kepada Masyarakat (JP-MAS)), 3(2), 592-597. Mayasiana, N. A., Dwimahendrawan, A., & Rohim. (2024). Digitalisasi Pelayanan Administrasi Kependudukan Dalam Mewujudkan Smart Village. Jurnal Pengabdian Kepada Masyarakat Nusantara (JPkMN), 6(1), 1871-1879. NW, A. C., Handika, J., Hariadi, S., & Helilintar, R. (2025, January). Implementasi Sistem Informasi Desa dalam Konsep Smart Village. In Seminar Nasional Teknologi & Sains (Vol. 4, No. 1, pp. 11-24). Permadi, I. B., & Rokhman, A. (2023, June). Implementasi Identitas Kependudukan Digital dalam Upaya Pengamanan Data Pribadi. JOPPAS: Journal of Public Policy and Administration, 4(2), 80-88. Ramjaya, I. G. M., Paramitha, A. I. I., & Eka Putra, I. G. J. (2024). Digitalisasi Data Kependudukan dan Pemutakhiran OpenSID Desa Tampaksiring Kabupaten Gianyar. BERNAS: Jurnal Pengabdian Kepada Masyarakat, 5(4), 2320-2328. Safitri, D. D., & Adnan, M. F. (2025). Partisipasi Masyarakat Dalam Penggunaan Layanan Mandiri Pada Sistem Informasi Desa (SID) Di Desa Marunggi Kecamatan Pariaman Selatan. Jurnal Administrasi Pemerintahan Desa, 6(1). Sulaeman, a. (2005). Difusi teknologi: teori, pendekatan, dan pengalaman (1st ed.). Pusat Pengkajian Kebijakan Difusi Teknologi, Badan Pengkajian dan Penerapan Teknologi.    Utomo, B. T., & Damanhuri, A. S. (2025, February). SISTEM INFORMASI DESA BERBASIS WEB (STUDI KASUS DESA DAYEUHKOLOT KABUPATEN SUBANG). In Global (Vol. 12, No. 1, pp. 16-24). Wardhani, M., & Mawansyah, J. (2025). Analisis Implementasi Sistem Informasi Desa Berbasis Smart Village dalam Mendukung Transformasi Digital di Pedesaan: Studi Kasus: Desa Sukadamai. Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 19(1), 57-64. Wijoyo, H., Cahyono, Y., Ariyanto, A., & Wongso, F. (2020). Digital Economy Dan Pemasaran Era New Normal. In Insan Cendekia Mandiri. Pemerintah Indonesia 2009. Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik. Pemerintah Indonesia 2023. Permendesa Nomor 7 Tahun 2023 Tentang Prioritas Penggunaan Dana Desa. Pemerintah Indonesia 2014. Undang-Undang Nomor 6 Tahun 2014.Tentang Desa.